DEVELOPMENT OF SUSTAINABLE PALM OIL FARMING IN THE KRUENG KEREUTO WATERSHED - Halim Akbar; Muhammad Authar ND; Anwar Puteh (RADJA PUBLIKA, 2023)
This research was conducted in the Krueng Kereuto watershedfrom October - November 2022. The objectives of this study were: to assess the suitability of land for oil palm plantations, to examine the effect of oil palm-based farming types on erosion and to analyze agrotechnology. The observation locations are on land map units 1, 3, 4, 5, 20, 21, 24, 25, 26, 27 and 28. The research method used in this research is a survey method which consists of four stages, namely: 1) the preparation stage 2) preliminary survey stage, 3) main survey stage and 4) data analysis and results presentation stage.The results showed that the assessment of land suitability for oil palm plantations in the Krueng Keureto watershed consisted of a moderately suitable class (S2) and a marginal suitable class (S3), with the limiting factor for oxygen availability (oa), namely obstructed drainage, nutrient retention limiting factor (nr) namely base saturation, pH and C-organic and the limiting factor for erosion hazard (eh) is the slope.The results of the erosion calculation show that the highest erosion prediction value occurs in the use of mixed gardens and shrubs.The predictive value of erosion on scrub land use (SST 3, 4, 5) ranged from 11.82 - 192.04 tonnes ha-1yr-1. This value is still far above the tolerable erosion value (ETol), which is 21.50 - 24.96 tons ha-1 year-1. Erosion prediction on mixed garden land use (SST 1, 20 and 21) ranges from 27.50 - 365.38 ton ha-1 year-1, this prediction value is still above the ETol value, namely 15.50 – 20.40 tons ha-1 year-1.